Perubahan Sifat Kimia Tanah Tercemar Merkuri Dengan Berbagai Modifikasi Pemberian Biochar Dan Tanaman Akar Wangi (Vetiveria zizanioides (L.) - Aprianti, Irma; Suwardji, Suwardji; Sukartono, Sukartono; Mulyati, Mulyati; Kusnarta, IGM. (LPPM Universitas Mataram, 2024)
The aims of this research is to determine changes in the chemical properties of mercury-contaminated soil with various modifications in the application of corn cob biochar and vetiver grass (Vetiveria zizanioides (L.). This research used an experimental method with an ex-situ remediation approach which was carried out from October 2023 to January 2024 in greenhouse. Sampling of mercury-contaminated soil was carried out on former traditional gold mining land in Segubuk Hamlet, Kuang Village, Taliwang Sub-District, West Sumbawa Regency. Soil sampling was taken from 13 locations determined by purposive sampling and carried out using a soil drill. Soil pH H2O, C-organic and CEC as well as analysis of the total concentration of mercury (Hg) in the soil were analysed before and after the experiment. The results showed that the application of corn cob biochar alone and corn cob biochar planted with vetiver grass (Vetiveria zizanioides (L.) had a significant effect) on changes in soil chemical properties and was effective in reducing the concentration of mercury (Hg) in the soil. Corn cob biochar application can improve soil chemical properties by increasing soil pH, organic C, and soil CEC. On the other hand, the release of H+ ions from the carboxyl functional group (-COOH) in corn cob biochar has the opportunity to form complexes with heavy metal ions so that it can reduce their concentration of mercury in the soil.